Exploring the Impact of Inlet Velocity Distribution on the Thermal Performance of a Laser Rod in a Diode Side-Pumped Amplifier - Shuzhen Nie; Jinglan Lin; Tianzhuo Zhao; Xiaolong Liu (Photonics)
Research on the thermal analysis of laser diode (LD) side-pumped amplifiers is a critical step in the design of high-power solid-state laser systems. Instead of adopting a standard solid modeling approach that only considers a laser rod, a fluid–structure interaction model is employed for analysis using the FLUENT 2021 R1 software. This model integrates the cooling structure, coolant, and laser rod, incorporating their relevant material parameters. By considering both uniform and non-uniform inlet velocity distributions as loading conditions, the study reveals remarkably different thermal simulation results. The correlation between thermal analysis outcomes and the total inlet flow rates is calculated, while temperature and stress distributions are obtained under a varying internal heat source. It was observed that the non-uniform inlet velocity distribution has little impact on the rod’s maximum temperature but significantly influences the maximum equivalent stress. This finding underscores the necessity of accounting for non-uniform inlet distributions during the design of laser amplifiers to achieve more accurate thermal simulation results and optimize structural reliability.